Circulating water leakage detection device for oxygen lance of Kaldo furnace - ZHOU GUNJIANG; DU YANJUN; WANG LI; LEI GUOQIANG; BAI MINGXUAN; YU LINA; TIAN FEI; LIU XINGTAO; AN GUORUI; ZHANG SHUBIN; ZHOU HELI (2023)
The utility model provides a Kaldo furnace oxygen lance circulating water leakage detection device which comprises an oxygen lance body, a circulating water jacket is arranged on the oxygen lance body, the circulating water jacket is connected with a water inlet pipe, the water inlet pipe is connected with a heat exchanger, the heat exchanger is connected with a water conveying pipe, the water conveying pipe is connected with a detection tank, and the detection tank is connected with a water pump. A water level sensor is arranged on the detection tank, the water level sensor is connected with a controller, the controller is connected with an alarm, the middle part of the detection tank is connected with a water return pipe, and the water return pipe is connected with the circulating water jacket. The detection tank is arranged on the water return pipe, the water level sensor is arranged on the detection tank, when water leakage occurs, the water level in the detection tank is lowered, the controller controls